Diabetes Fever - Sanjay Kalra; Suneet Verma; Nitin Kapoor; Saptarshi Bhattacharya (Journal of the Pakistan Medical Association, 2024)
While diabetes manifests multiple clinical presentations, complications and comorbidities, most modern discourse focuses on the cardiovascular aspects of the syndrome. In this communication, we explore the vast spectrum of fever and diabetes. We highlight the bidirectional interactions between febrile illness and diabetes, as well as drug-drug interactions. These multifaceted connections must be understood by all health care professionals who manage diabetes and/or fever. Keywords: Glycaemia, hyperglycaemia, infectious disease, pyrexia, tropical disease